Analisis Faktor-Faktor yang Mempengaruhi Tingginya Tingkat Kehadiran Pemuda-Pemudi Dalam Beribadah Di GEPKIN Tarutung Kota Dan Implikasinya Pada Gereja Kristen Protestan Indonesia (GKPI) Partapaan - Ita Marican Sinaga; Megawati Manullang; Jungjungan Simorangkir (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The level of attendance of young people attending worship services at GEPKIN Tarutung City has increased. According to the author's observations, this is influenced by several factors such as: music, interesting sermons, welcoming guests, and variations in service. The method used by researchers is a qualitative descriptive approach. The research implementation uses procedures that produce descriptive data in the form of written and spoken words from people whose behavior is observed through interviews or observations using a qualitative approach. This research aims to determine the factors that influence the high level of attendance of young people in worship at GEPKIN Tarutung City. From the research results, it can be seen that the factors of music, interesting sermons, welcoming guests, variety of services can increase the high attendance of young people in worship at GEPKIN Tarutung city. With the factors that influence the high level of attendance of young people, it can increase the presence of young people in worship at GEPKIN Tarutung city.